D.H. Lawrence, Science and the Posthuman - Wallace, J. author. aut Link
XI, 264 p.
Keywords: Why was D.H. Lawrence preoccupied with the enigma of the human as thinking matter? This first sustained study of Lawrence and science shows how 'posthuman' conceptions of a material kinship between humans, animals and machines can transform our understanding of Lawrence's work and of its complex relationship with scientific epistemologies. Through detailed readings of evolutionary philosophy, and of the 'new Bergsonism' of Deleuze and others, Wallace provides a radical reappraisal of Lawrence in terms of an 'antihumanist (or posthumanist) humanism' (Hardt and Negri).